ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADA KELOMPOK TANI AR-RIDHA DI DESA MOROME KECAMATAN KABUPATEN KONAWE KONDA SELATAN - Lely Okmawaty Anwar; Akhmad Akhmad; Mustam Mustam; Iin Nurdiyanti Nurdin; Dustan Dustan; Eko Aprianto Johan; Asjun Asjun (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
This research aims to determine the condition of livestock corn farming in the Ar-Ridha farmer group in Morome village, Konda District, South Konawe Regency during one planting season. Determining the sample in this research was using the census method. Data collection techniques through interviews using questionnaires with all members of the Farmer Group (22 Respondents). To determine the influence of production factors on farming, quantitative analysis of multiple linear regression is used. The most dominant group of Ar-Ridha Farmers is aged 21-30 years (31.8%), 100% are men, the education level of members of the Ar-Ridha Farmers Group is in the high category and 59.1% of members of the Ar-Ridha Farmers Group are in in the category of quite experienced in farming. The multiple linear regression mathematical model in this research is Production = 0.299-0.056 Seeds + 0.001 P.Organic - 0.001 P.Urea + 0.021 Farming Experience. The variables of using seeds, organic fertilizer, urea fertilizer, and farming experience together/simultaneously provide a very strong contribution/correlation in influencing livestock corn production results. 73.4% of the variation in production levels is influenced by the variables use of seeds, organic fertilizer, urea fertilizer, and farming experience, the remaining 26.6% is influenced by other variables. The factors of using seeds, organic fertilizer, urea fertilizer, and farming experience simultaneously have a significant effect on livestock corn production results.